Effects of aerobic capacity, age and gender on brain neural matter - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
The brain is one of the most complex and integrated organ in the human body which directs our muscle movements, our breathing and internal temperature, furthermore every imaginative sight, perception, and diagram are derived by the brain. The brain's neurons are effected by internal and external stimulations. Those stimulations might have positive and negative influence on brain activity and structure. There are several factors which can increase the activation of the brain, as well as increase gray matter (GM) and white matter(WM) volume, in some regions of the brain, such as learning new language, playing musical instrument as well as performing physical exercise. Studies suggested that aerobic exercice can enhance brain plasticity and may decrease risk for developing brain diseases in older adults. In this research, the effect of three factors which are age, gender and aerobic fitness level on brain structure were investigated by means of tissue volumes. Higher aerobic capacity did not indicate a change in structural volumetric brain volume. Moreover age-related gray matter (GM) atrophy was significantly observed. Finally, greater hippocampal volume in female volunteers was found when compared to male volunteers. © 2017 IEEE.
Keywords: age; brain structure; gender; gray matter; MRI; VO2 max